A guide to presenting technical information : effective graphic communication / Clifford Matthews. - Matthews, Clifford (Professional Engineering, 2000)
Choosing the most appropriate graphics, tables & diagrams is a valuable skill for anyone involved in engineering, science or technology. This practical guide includes step-by-step treatment to help improve the quality of your output